SPECIAL AND INCLUSIVE EDUCATION: THE ROLE OF THE SCHOOL IN WELCOMING STUDENTS WITH SPECIAL NEEDS - Mirele Alves Medeiros, Maria; Willames Cirino Oliveira, Wesley (Revista Gênero e Interdisciplinaridade, 2024)
This paper aims to present the challenges imposed on educational institutions that seek to adapt to the learning needs of students with special needs. A special and inclusive education that aims at the development of multiple skills through innovations and inclusive pedagogical practices. Where it is necessary to implement public policies inside and outside the school environment that will support the process of inserting these students into regular education classes, as they have a right to, as well as individual and specialized monitoring so that they can develop their potential. Here, we highlight the struggles and achievements that permeate the history of these people who so much seek their rights, having the validity of the process of change that is necessary in the search for a meaningful education. Thus, the objective of this work is to present the role of the school as an inclusive space that brings together, respects and welcomes differences, where it is necessary to subsidize the necessary resources for the improvement of new practices, with trained professionals, an inclusive education that serves students in their entirety, from physical resources, highlighting the school structure itself, to specific teaching materials and the various resources that support this process.